INVESTIGATING THE BARRIERS OF OPEN EDUCATIONAL RESOURCES ADOPTION AMONG UNIVERSITY TEACHERS - Finhas Masih; Dr. Ghulam Dastgir; Ateeq Ur Rehman; Hina Gulzar; Rab Nawaz (International Journal of Contemporary Issues in Social Sciences, 2023)
The study was conducted to investigate the main barriers to implementation of Open Educational Resources (OERs). The study was analyzed the barriers which were made hurdles to adopt OERs among university teachers. OERs refer to teaching and learning materials accessible to everyone. They can be used by students, teachers, and researchers without any cost. Nowadays, in our digital era, OERs have become really important in universities. Keeping in view the importance of OERs, The study was designed to assess the barriers for implementation the OERs among university teachers. A quantitative research method using a survey design was adopted to meet the research objectives. The researcher adopted this method to collect the data from the participants through questionnaires; descriptive analysis was chosen for completion. There were 200 participants with equal sampling strata (male = 50%, female = 50%). The data were gathered using a self-developed questionnaire after ensuring its reliability and validity. In this study, it is investigated the various factors influencing teachers’ perceptions and utilization of open educational resources (OER), which encompass educational materials accessible to all. Our findings revealed a multitude of interconnections, including disparities between male and female educators, age-related dynamics, and the duration of a teacher’s career. Notably, male teachers demonstrated greater technological proficiency and a deeper understanding of OER, highlighting the need for targeted support to empower female educators in OER adoption. Younger teachers, those under 26 years old, displayed a heightened interest in OER, suggesting the importance of further facilitating their engagement with these resources. Additionally, the tenure of a teacher played a significant role, with those teaching between 6 to 15 years being more inclined to incorporate OER into their practices. However, certain apprehensions regarding the challenges associated with OER usage hindered some teachers, necessitating efforts to streamline accessibility. In summary, our study underscores the importance of considering factors such as gender, age, experience, and barriers to promote the widespread integration of OER in education, potentially revolutionizing learning for all.